Consumer Consciousness in Multisensory Extended Reality - Petit, Olivia; Velasco, Carlos; Wang, Qian Janice; Spence, Charles (Frontiers in Psychology, 2022)
The reality-virtuality continuum encompasses a multitude of objects, events and environments ranging from real-world multisensory inputs to interactive multisensory virtual simulators, in which sensory integration can involve very different combinations of both physical and digital inputs. These different ways of stimulating the senses can affect the consumer’s consciousness, potentially altering their judgements and behaviours. In this perspective paper, we explore how technologies such as Augmented Reality (AR) and Virtual Reality (VR) can, by generating and modifying the human sensorium, act on consumer consciousness. We discuss the potential impact of this altered consciousness for consumer behaviour while, at the same time, considering how it may pave the way for further research.